PROFILE OF ACADEMIC HARDINESS IN SANTRI IN PARUNGPONTENG SUB-DISTRICT - Naopal, Zaki Ahmad; Muhajirin, Muhammad; Nugraha, Agung (Jurnal Kajian Pendidikan dan Psikologi, 2024)
This research is motivated by the phenomenon that occurs due to the lack of academic resilience in students, making students uncomfortable living in Islamic boarding schools and causing stress in the students. This study aims to describe the general picture of academic resilience in students in the Parungponteng sub-district. The characteristics of students who have moderate academic resilience are being able to see stressful events as positive stressors for development and having strong psychological resilience. The characteristics of students who have high academic resilience are being able to survive in facing their academic challenges and seeing stressful events as positive stressors for development, and the characteristics of students who have low academic resilience are being easily stressed, not strong against existing pressure, lack of self-confidence in their academic abilities and less resilient to challenges that arise from their friendship and social environment. The research conducted on the general picture of academic resilience in students in the Parungponteng sub-district is in the high category. Based on the results shown, the highest value is in the medium category with a percentage score of 76.58% with a frequency of 170 students, and academic resilience in students in the Parungponteng sub-district whose category high is 22.52% with a frequency of 50 students. And a score of 0.90% in the low category with a frequency of 2 students. The number of samples in this study was N = 222. This research method uses descriptive statistics, namely statistics used to analyze data by describing or depicting data that has been collected as it is without intending to make conclusions that apply to the public or generalizations.